Analysis of the theory of planned behavior on the use of halal-labeled cosmetics for students at the University of Islamic Malang - Ma'ruf, Muhammad; Salamah, Nina (Universitas Ahmad Dahlan, 2023)
The practice of using halal cosmetics involves the intentional involvement of individuals, groups, or organizations in acquiring and using cosmetics that have obtained a halal certification. The behavior of individuals is subject to influence by multiple factors, including attitudes, subjective norms, behavioral control, and intention to use. These factors are motivated by the desires and needs of the individual. This study examines the influence of attitudes, subjective norms, behavioral control, and usage intentions on adopting halal-labeled cosmetics among college students. This research investigates the impact of attitudes, subjective norms, behavioral management, and usage intentions on adopting cosmetics labeled as